Generation of Cosmic rays in Historical Supernova Remnants - Sinitsyna V.Y.; Sinitsyna V.G. (EPJ Web of Conferences, 2013)
We present the results of observations of two types of Galactic supernova remnants with the SHALON mirror Cherenkov telescope of Tien-Shan high-mountain Observatory: the shell-type supernova remnants Tycho, Cas A and IC 443; plerions Crab Nebula, 3c58(SN1181) and Geminga (probably plerion). The experimental data have confirmed the prediction of the theory about the hadronic generation mechanism of very high energy (800 GeV - 100 TeV) gamma-rays in Tycho's supernova remnant. The data obtainedsuggest that the very high energy gamma-ray emission in the objects being discussedis different in origin.